Assessing starch digestibility and carbohydrate quality of Ugandan maize varieties: implications for diet-related non-communicable diseases risk - Fassinou, Finagnon Toyi Kevin; Olum, Solomon; Ongeng, Duncan (Taylor & Francis group, 2025)
Low-carbohydrate-quality food consumption increases risk of the development of diet-associated non-communicable diseases (NCDs). Although maize is a major dietary carbohydrate source food consumed by 92% of households in Uganda, its carbohydrate quality is largely unknown. This study examined starch digestibility, carbohydrate quality, and the contents of associated intrinsic physico-chemical factors that influence starch digestibility for thirteen (13) maize varieties commonly consumed in Uganda. In general, the maize varieties examined had a carbohydrate-to-crude fiber ratio ranging from 5.28 to 10.15 and exhibited high glycemic indices in the range of 79.38 to 86.27, indicating low carbohydrate quality. The physico-chemical factors that influence starch digestibility varied significantly (p < 0.05) across varieties. Hierarchical cluster analysis grouped the varieties into four significantly different clusters based on the level of chemical factors that influence (p < 0.05) starch digestibility. Cluster composed of varieties DT MAX, Longe 5D, and WE3106 had the best matrix combination of physico-chemical characteristics associated with better starch resistance. This study has revealed that maize varieties consumed in Uganda have low carbohydrate quality, which suggests that their consumption is a risk factor for diet-associated non-communicable diseases in the country and surrounding countries. A concerted effort is necessary to improve the carbohydrate quality of the maize varieties.
Keywords: digestibility; glycemicindex; metabolic diseases; resistant starch